Multicamadas de ZnO aplicadas a dispositivos memresistores - Santos, Yvens Pereira dos (2019)
We present a study on the applicability of multilayer films based on ZnO as memresistors devices. Two groups of films were produced by the Sputtering deposition technique. In the group I (ITO/ZnO/Fe/ZnO and ITO/ZnO/Fe/ZnO/Fe/ZnO) samples were analyzed by X-ray diffractometry (XRD), scanning electron microscopy (SEM) and magnetization measurements using a vibrating sample magnetometer (VSM), X-ray refletometry (RRX), and an electrical characterization. The samples presented a good performance as memresistor device, with good resistive state retention time (4 × 103s) and differentiation between expressive states, it was also determined the main conduction mechanism present in the sample. We identified the sample thicknesses using the SEM technique that had a good agreement with RRX. The magnetization measurements revealed the presence of weak ferromagnetic behavior at room temperature attributed to the presence of Fe in the film, resistivity measurements as a function of the field suggest the possible presence of giant magnetoresistance effect in the samples. For group II (ITO / ZnO / Gd2O3 / ZnO) was performed the electrical characterization of the samples that indicated the degradation of the memresistor effect proportionally to the increase of Gd2O3 layer deposition time.